TLR2 activated B cells are phenotypically similar to the abnormal circulating B cells seen preceding the diagnosis of AIDS related non-Hodgkin lymphoma (NHL) diagnosis - Guo, Yu (2013)
BACKGROUND: AIDS-related non-Hodgkin lymphoma (AIDS-NHL) is a common AIDS-defining cancer. Prior studies suggest that chronic B cell activation precedes AIDS-NHL diagnosis. Activation of B cells by multiple factors, including Toll-like receptor (TLR) signaling, leads to the expression of activation-induced cytidine deaminase (AID), a DNA mutating molecule that can contribute to oncogene translocations/mutations, leading to NHL. The goal of this study was to determine whether surface markers expressed on activated and/or germinal center (GC) B cells, and AID expression, were elevated on circulating B cells preceding AIDS-NHL, as well as to determine if TLR signaling contributes to this activated B cell phenotype. METHODS: Stored viable peripheral blood mononuclear cell (PBMC) specimens, obtained prior to AIDS-NHL diagnosis, were assessed by multi-color flow cytometry. Additionally, B cells isolated from PBMC were exposed to TLR ligands in vitro, after which B cell phenotype was assessed by flow cytometry. RESULTS: An elevated fraction of B cells expressing CD10, CD71, or CD86 was seen in those who went on to develop AIDS-NHL. AID expression was detected in some who developed AIDS-NHL, but not in HIV+ or HIV− controls. TLR2- stimulated purified B cells exhibited the activated B cell phenotype observed in HIV+ subjects prior to AIDS-NHL diagnosis. CONCLUSIONS: These results indicate that an elevated fraction of B cells display an activated/GC phenotype in those HIV+ subjects who go on to develop AIDS-NHL, and suggest that TLR2-mediated activation may play a role in HIV infection-associated B cell activation, potentially contributing to the genesis of AIDS-NHL.